Factors affecting online purchasing behaviour among Muslim Consumers in Selangor / Nur Aida Hasim - Hasim, Nur Aida (Faculty of Business and Management, 2019)
This paper is conduct to look at the factors affecting online purchasing behaviour amongst Muslim consumers. The population of this examine is Malaysian and sample of study (respondent) is among Muslim consumers in Selangor. Sampling approach is convenience sampling and the usage of questionnaire to collect the facts. Statistical package for Social Science (SPSS) use to analyse the statistics and method for examine the data is by the usage of Frequency analysis, Descriptive analysis, Multiple Linear Regression, Correlation Analysis and Reliability Analysis (Cronbach's Alpha). The questionnaire could be distribute to 250 Muslims in Selangor. The questionnaire focus on the independent variables, which include perceived benefits, perceived risks, hedonic motivations, psychological factors and website design whilst the dependent variable is online shopping behaviour. The researcher of the study experts to know whether independent variables of perceived advantages, perceived risks, hedonic motivations, psychological factors and website design are significant with the dependent variable, online purchasing behaviour.